2020
DOI: 10.3389/fmars.2020.00085
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Complementarity Between a Brown Alga and Associated Cultivable Bacteria Provide Indications of Beneficial Interactions

Abstract: Brown algae are key components of marine ecosystems and live in association with bacteria that are essential for their growth and development. Ectocarpus siliculosus is a genetic and genomic model for brown algae. Here we use this model to start disentangling the complex interactions that may occur between the algal host and its associated bacteria. We report the genome-sequencing of 10 alga-associated bacteria and the genome-based reconstruction of their metabolic networks. The predicted metabolic capacities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The relevance of MiSCoTo ( Frioux et al, 2018 ), the algorithm for minimal community selection used in M2M, has been recently experimentally demonstrated. It was applied to design bacterial communities to support the growth of a brown alga in nearly axenic conditions ( Burgunter-Delamare et al, 2019 ). Despite the difficulty inherent to controlling the communities for a complex alga, the inoculated algae exhibited a significant increase in growth and metabolic profiles that at least partially aligned with the predictions, demonstrating the versatility in application fields of our methods.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of MiSCoTo ( Frioux et al, 2018 ), the algorithm for minimal community selection used in M2M, has been recently experimentally demonstrated. It was applied to design bacterial communities to support the growth of a brown alga in nearly axenic conditions ( Burgunter-Delamare et al, 2019 ). Despite the difficulty inherent to controlling the communities for a complex alga, the inoculated algae exhibited a significant increase in growth and metabolic profiles that at least partially aligned with the predictions, demonstrating the versatility in application fields of our methods.…”
Section: Discussionmentioning
confidence: 99%
“…One consequence of the development of such new methods is the feedback they provide to improve existing models or to develop entirely new ones, e.g., by conceptualizing holobionts as the combination of the interactions between the host and its microbiota ( Skillings, 2016 ; Berry & Loy, 2018 ), or by redefining boundaries between the holobiont and its environment ( Zengler & Palsson, 2012 ). Such models may incorporate metabolic complementarity between different components of the holobiont ( Dittami, Eveillard & Tonon, 2014 ; Bordron et al., 2016 ), e.g., enabling the prediction of testable metabolic properties depending on holobiont composition ( Burgunter-Delamare et al., 2020 ), or simulate microbial communities starting from different cohorts of randomly generated microbes for comparison with actual metatranscriptomics and/or metagenomics data ( Coles et al., 2017 ).…”
Section: Challenges and Opportunities In Marine Holobiont Researchmentioning
confidence: 99%
“…Bacteria can be associated with the surface, the holdfast, or the chemical boundary layer of the alga in the surrounding water (Mieszkin et al, 2013;Egan et al, 2014;Wichard, 2015). Based on different scenarios, chemical compounds produced on macroalgal surface or its vicinity may present the primary factors driving the dynamic of bacterial communities within the network of algae-bacteria interactions (Lachnit et al, 2013;Kessler et al, 2018;Alsufyani et al, 2020;Burgunter-Delamare et al, 2020;Paix et al, 2020). Employing a multi-omics approach on the thallus scale demonstrated that chemical production, which is mostly stimulated by the algal physiology, defines the microbial community structure and composition at the surface of individual thalli of Taonia atomaria.…”
Section: Chemically-mediated Bacterial-macroalgal Interactionsmentioning
confidence: 99%
“…Tools in phycology and genetics can be combined with systems biology to increase our understanding of the mutualistic interaction of the holobiont in adaptation processes. Thus, the metabolic complementarity of host and symbionts could be an excellent marker for beneficial interactions as outlined by Burgunter-Delamare et al (2020). A combination of "putting pieces apart" (reductionist biology) and "putting pieces together" (systems biology) seems thus to be the most promising approach to understanding the evolution of system properties in the phycosphere.…”
Section: Perspectives In Microbiome Engineeringmentioning
confidence: 99%